2018
DOI: 10.1038/s41598-018-21573-w
|View full text |Cite
|
Sign up to set email alerts
|

Common Deregulation of Seven Biological Processes by MicroRNAs in Gastrointestinal Cancers

Abstract: MicroRNAs are frequently dysregulated in human neoplasms, including gastrointestinal cancers. Nevertheless, the global influence of microRNA dysregulation on cellular signaling is still unknown. Here we sought to elucidate cellular signaling dysregulation by microRNAs in gastrointestinal cancers at the systems biology level followed by experimental validation. Signature dysregulated microRNAs in gastric, colorectal and liver cancers were defined based on our previous studies. Targets of signature dysregulated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 59 publications
(48 reference statements)
1
6
0
Order By: Relevance
“…The adaptive immune response pathway was correlated with a number of down-regulated miRNAs in our PDAC dataset: 8/20 (40%) miRNAs identified in our study directly target genes in this pathway. Specifically, members of miR-216 family (miR-216a-5p, miR-216a-3p and miR-216b-5p) and miR-217 target CD antigens including LILRB1 and LILRB4 [51], CD36, CD160 [52], CD226 [53], CD300LB and SIGLEC10 [54] as well as toll-like receptor TLR6. In the context of the tumor microenvironment, gene expression alterations may be dependent on post-transcriptional regulatory mechanisms such as miRNAs, which have been shown to regulate the recruitment and activation of immune cells to the tumor [12].…”
Section: Discussionmentioning
confidence: 99%
“…The adaptive immune response pathway was correlated with a number of down-regulated miRNAs in our PDAC dataset: 8/20 (40%) miRNAs identified in our study directly target genes in this pathway. Specifically, members of miR-216 family (miR-216a-5p, miR-216a-3p and miR-216b-5p) and miR-217 target CD antigens including LILRB1 and LILRB4 [51], CD36, CD160 [52], CD226 [53], CD300LB and SIGLEC10 [54] as well as toll-like receptor TLR6. In the context of the tumor microenvironment, gene expression alterations may be dependent on post-transcriptional regulatory mechanisms such as miRNAs, which have been shown to regulate the recruitment and activation of immune cells to the tumor [12].…”
Section: Discussionmentioning
confidence: 99%
“…Equal amounts of protein were separated via SDS-PAGE in the presence of SeeBlue Plus2 Pre-stained Protein Standard (Thermo Fisher) followed by western transfer onto PVDF membrane. Membrane was blocked with 5% skim milk powder in 1 × PBS followed by overnight incubation with the primary antibodies to Alix [3A9] (Cell Signaling Technology, Danvers, MA) 32 , ARF6 [ab77581] (Abcam, Cambridge, UK) 33 , CD81 [M38] (Life technologies) 34 and Calreticulin [ab22683] (Abcam) 35 in 1% BSA in PBST at 4 °C, followed by three 10 min wash steps in PBST. Membranes were then incubated with HRP-conjugated sheep anti-mouse antibodies (1:5000, Millenium Science), Li-Cor goat-anti rabbit or goat anti-mouse IRDye 800CW (1:10000, Millennium Science) in 1% BSA in PBST for 1 h at RT, followed by washing as described for primary antibodies.…”
Section: Methodsmentioning
confidence: 99%
“…In gastrointestinal cancers like gastric, colon and liver cancers, microRNAs can regulate not only known cancer-related signaling pathways but also some other processes such as axon guidance, neurotrophin/nerve growth factor signaling, and endocytosis. Zhang et al (120) confirmed regulation of EGF receptor (EGFR) endocytosis by miR-17 and miR-145, predicted to target endocytosis. While miR-17 promoted, miR-145 inhibited the internalization of EGFR upon EGF binding to the plasma membrane in human colon cancer cells SW1116.…”
Section: Micrornas Regulating Clathrin-mediated Endocytosismentioning
confidence: 99%
“…While miR-17 promoted, miR-145 inhibited the internalization of EGFR upon EGF binding to the plasma membrane in human colon cancer cells SW1116. Blocking of EGFR endocytosis by miR-145 resulted in prolonged EGFR membrane signaling and altered responsiveness of colon cancer cells to EGFR-targeting drugs (120).…”
Section: Micrornas Regulating Clathrin-mediated Endocytosismentioning
confidence: 99%